(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
The objectives of this research are to classify the type of slang words, to work out the contextual meaning of slang words, and to spot the functions of slang in Ramona and Beezus movies. This research used a descriptive qualitative method. The source of data of this research used the movie and also the dialogue of the movie. The result showed that there are 47 slang words in Ramona and Beezus movies. The researcher found that the slang words are formed based on the types of slang those are, fresh & creative, flippant, imitative, acronym, clipping. The second of finding was about the social factors and social distant set the contextual meaning of slang words, which are participant and the subject of conversation. As for the third finding, five functions of slang words was found within the movie which are to address, to humiliate, to initiate relaxing conversation, to show impression, and to reveal anger.